Internasionalisasi Bahasa Indonesia Melalui Kuliner Tradisional “Gulai” sebagai Bahan Ajar Bahasa Indonesia bagi Penutur Asing Berbasis Kearifan Lokal - Jovita Ratu Parosa; Fitri Nur Rahmawati; Khazimah Ila Salsabila; Orisa Sativa; Kundharu Saddhono (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study aims to analyze the potential of Indonesian culinary "Gulai" as a BIPA teaching material and to introduce Indonesian culture through traditional food. The method used in this study is a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study indicate that through the culinary learning media "Gulai" in the BIPA program can overcome the lack of teaching materials. Through the culinary teaching material "Gulai" in addition to promoting Indonesian language and culture, it can also add educational value and cultural value to BIPA teaching materials to be introduced to BIPA learners. This study focuses on the development of internationalization studies of the Indonesian language by utilizing traditional culinary as a learning medium by considering the global appeal, historical value, and diversity of traditional food flavors.